2014
DOI: 10.4103/0976-3147.139966
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical stroke scores for distinguishing stroke subtypes in resource poor settings: A systematic review of diagnostic test accuracy

Abstract: Background:Stroke is the second leading cause of death globally. Computerized tomography is used to distinguish between ischemic and hemorrhagic subtypes, but it is expensive and unavailable in low and middle income countries. Clinical stroke scores are proposed to differentiate between stroke subtypes but their reliability is unknown.Materials and Methods:We searched online databases for studies written in English and identified articles using predefined criteria. We considered studies in which the Siriraj, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…This increases the predictive ability of the score to identify an ischemic stroke. For example, Mwita et al[ 10 ] in a systematic review reported consistently higher specificities of the SSS with a range from 65%–99% compared to its corresponding sensitivities in 18 validation studies. This is in agreement with our specificity findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increases the predictive ability of the score to identify an ischemic stroke. For example, Mwita et al[ 10 ] in a systematic review reported consistently higher specificities of the SSS with a range from 65%–99% compared to its corresponding sensitivities in 18 validation studies. This is in agreement with our specificity findings.…”
Section: Discussionmentioning
confidence: 99%
“…The simplicity of this score and its practical application has been commended in several studies. [ 5 , 10 ] Nevertheless, we are aware that the recalibrated SSS may not be easily memorized or applied without a calculator. Future implementation of this score with a possible smartphone application will be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a systematic meta-analysis by Mwita et al . [ 9 ] questioned the accuracy of clinical stroke scores for distinguishing stroke subtypes in resource-poor settings. To the best of our knowledge, none of these score systems have been validated in Chinese stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of Guy's Hospital stroke score for hemorrhage stroke is 96.4%, specificity is 100%, accuracy 97.1%, positive predictive value of 100% and negative predictive value 87.5%. Mwitaet al26 reported sensitivity for ischemic stroke ranged from 0.25 to 0.93 while specificity ranged from 0.50 to 0.97. Overall, sensitivity for the test was 0.7 (95% CI 0.53 0.83) and specificity was 0.79 (95% CI 0.68 0.87) for ischemic stroke.…”
mentioning
confidence: 99%